Creating the Desire for Change in Higher Education The Amsterdam Path to the Research-Teaching Nexus - Griffioen, Didi (Bloomsbury Academic, 2022)
Focusing on change in higher education, and on furthering the integration of research and education, this open access book brings together and builds upon the international bodies of knowledge on higher education change and on the relationship between research and teaching. Rather than simply combining this knowledge, this book provides a thorough understanding of change paths towards sustainable hybrid higher education organizations of research and teaching. The contributors explore ways in which the model can work at the different levels of the higher education organisation, providing knowledge and understanding of creating an evidence-informed direction for institutional change towards the improved connection between research and education. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on www.bloomsburycollections.com. Open access was funded by Amsterdam University of Applied Sciences (AUAS), the Netherlands.